Job resources, job demands and developmental HR in relation with work engagement : the moderating role of service climate - Ahmed, Umair (2017)
Enterprises globally are facing the issue of work engagement whereby, dearth of research exists on how it could be addressed particularly in an emerging economy like Pakistan. Upon the explanations of Conservation of Resources (COR) theory; studies have indicated job demands and resources model (JD-R) as the most promising theoretical framework for understanding work engagement. Therein, the study investigated how job resources such as supervisor support, co-worker support and meaningful work, and job demands such as workload and emotional demands can influence work engagement. The study also tested developmental HR resources such as employee training opportunities, career development opportunities and developmental performance appraisal. Additionally, service climate was also empirically tested for potential moderating effect on these relationships. Results of the PLS path modelling of 277 employees from the banking sector of Pakistan, found significant direct relationships of co-worker support, meaningful work and developmental HR resources with work engagement. Meanwhile, job demands including such as workload and emotional demands resulted in negative relationships with work engagement. However, supervisor support was not significantly influences on work engagement. Furthermore, the bootstrapping results found significant moderation of service climate upon employee training opportunities and career development opportunities relationships with work engagement. On the flipside, the study did not find any moderation of service climate on job resources and job demands in their relationships with work engagement. The results show that work engagement can be enhanced through job and developmental HR resources whereas; job demands can potentially deplete it. Alongside, service climate can be of prominence for service sector to strengthen the developmental HR resources and work engagement relationships.